Analisis Kemampuan Retensi Air Karakteristik Akar Pohon Beringin sebagai Zona Penyangga Mata Air di Wilayah Kecamatan Aikmel, Lombok Timur - Sumaedi Sumaedi; Nining Tria (Lembaga Publikasi Ilmiah Nusantara, 2026)
Aikmel Subdistrict in East Lombok faces the threat of declining spring discharge due to land-use change and environmental degradation. This community service activity aims to educate residents and optimize the function of the banyan tree (Ficus benjamina) as a water conservation buffer zone, based on an analysis of its water retention capacity and root characteristics. The program's implementation method consists of three main stages: a vegetation survey and direct measurement of soil water retention capacity around the banyan root systems, educational dissemination to local forest farmer groups and youth, and direct action through planting banyan saplings around the catchment area. Field analysis results show that the banyan's root structure—comprising a deep taproot accompanied by a dense network of lateral fibrous roots—is capable of creating high soil porosity. This condition significantly increases the infiltration rate and surface soil water retention capacity, thereby effectively maintaining the stability of surrounding spring discharge. Through this program, community understanding regarding the ecological role of local vegetation increased significantly, shifting from a poor understanding to a thorough comprehension. Furthermore, a spring conservation group was formed, committed to protecting the vegetative buffer zone. In conclusion, integrating scientific understanding of banyan root characteristics with active community involvement creates a sustainable community-based water conservation model in Aikmel Subdistrict. This activity is expected to be replicated in other regions experiencing similar water crises.